2016
DOI: 10.1111/apm.12576
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment with the oncolytic ECHO‐7 virus Rigvir of a melanoma stage IV M1c patient, a small cell lung cancer stage IIIA patient, and a histiocytic sarcoma stage IV patient‐three case reports

Abstract: Alberts P, Olmane E, Brok ane L, Krastin ßa Z, Romanovska M, Kup cs K, Isajevs S, Proboka G, Erdmanis R, Nazarovs J, Venskus D. Long-term treatment with the oncolytic ECHO-7 virus Rigvir of a melanoma stage IV M1c patient, a small cell lung cancer stage IIIA patient, and a histiocytic sarcoma stage IV patient-three case reports. APMIS 2016; 124: 896-904 Oncolytic virotherapy is a recent addition to cancer treatment. Here, we describe positive treatment outcomes in three patients using Rigvir virotherapy. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 17 publications
0
43
0
1
Order By: Relevance
“…(66, 67) A retrospective study of Rigvir in patients with stage IB-IIC melanoma found that Rigvir significantly prolonged survival and reduced mortality, without record of any “untoward” side effects(68), and a case report showed prolonged survival in patients with stage IV M1c melanoma treated with Rigvir. (69) The case report data has limited applicability, as it was obtained retrospectively and lacked a control arm. However, given the potential specificity of this therapy for cancer cells, the safety and efficacy of Rigvir in the treatment of melanoma merits further investigation.…”
Section: Oncolytic Viruses Used In the Treatment Of Melanomamentioning
confidence: 99%
“…(66, 67) A retrospective study of Rigvir in patients with stage IB-IIC melanoma found that Rigvir significantly prolonged survival and reduced mortality, without record of any “untoward” side effects(68), and a case report showed prolonged survival in patients with stage IV M1c melanoma treated with Rigvir. (69) The case report data has limited applicability, as it was obtained retrospectively and lacked a control arm. However, given the potential specificity of this therapy for cancer cells, the safety and efficacy of Rigvir in the treatment of melanoma merits further investigation.…”
Section: Oncolytic Viruses Used In the Treatment Of Melanomamentioning
confidence: 99%
“…To assess patients for ADEs, we used the Common Terminology Criteria for Adverse Events (CTCAE) version 4, which was developed by the US National Cancer Institute [28][29][30][31], a method originally developed for the assessment of cancer patients undergoing chemotherapy. There are three general categories of adverse events (AEs) in the CTCAE: (1) laboratory-based events (e.g., hyponatremia), (2) observable/measurable events (e.g., hypotension), and (3) symptomatic adverse events (e.g., nausea) [31].…”
Section: Data Collectionmentioning
confidence: 99%
“…We used CTCAE to identify ADEs. This method is mainly used to classify adverse events in cancer patients undergoing chemotherapy [28][29][30], and less is known about its validity in a general geriatric population. However, we will argue that the methodology and structure of the instrument makes it feasible for elderly multimorbid patients as well.…”
Section: Sadementioning
confidence: 99%
“…To our knowledge, there are few reports about the effects of oncolytic viruses (morbillivirus and ECHO‐7 virus) on canine and human histiocytic sarcoma . Therefore, data on the oncolytic effects of reovirus on histiocytic sarcoma cells are expected to serve as important evidences for the rational use of oncolytic viruses in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are few reports about the effects of oncolytic viruses (morbillivirus and ECHO-7 virus) on canine and human histiocytic sarcoma. [17][18][19] Therefore, data on the oncolytic effects of reovirus on histiocytic sarcoma cells are expected to serve as important evidences for the rational use of oncolytic viruses in clinical trials. In the present study, we examined the oncolytic effects, both in vitro and in vivo, of reovirus on canine histiocytic sarcoma cell lines and on normal DCs derived from healthy dogs.…”
mentioning
confidence: 99%